Finding the silver lining : tolerance for contradiction, positive reframing, and gratitude during the COVID-19 pandemic - Wee, Darryl Pen Hao (Nanyang Technological University, 2021)
The COVID-19 pandemic has brought about a negative impact on people’s lives globally, especially on family relationships. However, some were able to find the silver lining amidst these challenges and develop better familial relationships. We sought to understand how individuals were able to see the good in the bad during the COVID-19 pandemic and the mechanisms they utilized to deal with stressful events. We predicted that individuals with a high tolerance for contradiction, compared to individuals with a low tolerance for contradiction, will experience more feelings of gratitude towards their family during the COVID-19 pandemic, through engaging in more positive reframing coping styles. 216 U.S. participants from MTurk were primed with either high or low tolerance for contradiction. We measured their tendency to engage in positive reframing using a rating scale, and the gratitude expressed towards their family in a letter. People with a high tolerance for contradiction, compared to people with a low tolerance for contradiction, experienced more feelings of gratitude towards their family. However, positive reframing did not mediate the relationship between tolerance for contradiction and gratitude. The findings suggest that people who have a high tolerance for contradiction and gratitude, compared to those with a low tolerance for contradiction, are expected to have better outcomes such as greater well-being and better relationships with their families as these mechanisms buffer against the stressors of the pandemic.